2021
DOI: 10.3389/fgene.2021.791640
|View full text |Cite
|
Sign up to set email alerts
|

HIF-Dependent NFATC1 Activation Upregulates ITGA5 and PLAUR in Intestinal Epithelium in Inflammatory Bowel Disease

Abstract: Intestinal epithelial cells exist in physiological hypoxia, leading to hypoxia-inducible factor (HIF) activation and supporting barrier function and cell metabolism of the intestinal epithelium. In contrast, pathological hypoxia is a common feature of some chronic disorders, including inflammatory bowel disease (IBD). This work was aimed at studying HIF-associated changes in the intestinal epithelium in IBD. In the first step, a list of genes responding to chemical activation of hypoxia was obtained in an in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
3
13
1
Order By: Relevance
“…Examination of DEGs and functional enrichment analysis revealed the LVBRS toolkit successfully recapitulated previously reported results [14]. Specifically, most DEGs in each study are the same (Table 3).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Examination of DEGs and functional enrichment analysis revealed the LVBRS toolkit successfully recapitulated previously reported results [14]. Specifically, most DEGs in each study are the same (Table 3).…”
Section: Resultssupporting
confidence: 78%
“…Using the LVBRS toolkit to reanalyze publicly available data, we recapitulated previously published results [14] and added additional biological insights by incorporating additional functional databases and alternative splicing analysis. For example, both studies identified the MSig term "HALLMARK_TNFA_SIGNALING_VIA_NFKB" to be enriched among DEGs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was reported that more HIF-1α and NFATc1 were expressed in hypoxic conditions ( 39 , 40 ). NFATc1 activation was dependent on HIF, and NFATc1 was upregulated in hypoxia ( 41 ). In the present study, HIF-1α was highly expressed in PD-1 + CD4 T cells after P. yoelii infection ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…After inflammation occurs, PLAUR binds to PLAU and activates plasminogen to plasmin, promoting inflammatory cell migration and activation and matrix metallopeptidase (MMP) activation, thereby participating in the inflammatory response ( 60 , 63 65 ). In addition, PLAUR can be regulated by the hypoxia-inducible factor HIF-1 to play a role in the hypoxia-related mechanisms of the disease ( 66 ). In this study, TIMP1 and PLAUR upregulation in ICH was validated in an independent cohort, which confirms the involvement of TIMP1 and PLAUR in ICH development.…”
Section: Discussionmentioning
confidence: 99%